IMPLEMENTING CIRCULAR ECONOMY IN WASTE MANAGEMENT THEORETICAL, PRACTICAL, AND PENTA HELIX PERSPECTIVES - Islami, Syaifuddin; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study explores the application of a circular economy in waste management policies in Indonesia from both theoretical and practical perspectives, utilizing a penta helix approach. Unlike linear economies that lead to unmanaged waste, a circular economy focuses on reusing, recycling, and reducing waste to achieve economic and environmental sustainability. The penta helix model, involving academia, businesses, communities, government, and media, plays a crucial role in enhancing public awareness and participation in sustainable waste programs. A qualitative case study approach was used to evaluate the effectiveness of current policies, identifying infrastructural challenges, public awareness gaps, and cross-sector collaboration opportunities. Findings suggest the need for improved recycling infrastructure, fiscal incentives for businesses, and intensive public awareness campaigns. The study concludes that the penta helix collaboration can accelerate Indonesia’s transition toward a more sustainable and environmentally friendly circular economy, with recommendations for enhanced cross-sector cooperation to support this shift.Keywords: Circular economy, waste management, penta helix, Indonesia, sustainability